Silencing the Stray Strands: Electrolysis to Tame Latrogenic Oral Hair Growth - Kritika Gupta; Sunil K. Gupta; Tanvi Agrawal; Rohit K. Singh (Indian Dermatology Online Journal, 2025)
Intraoral hair growth following flap reconstruction for oral cancer surgery is a common but often overlooked complication. This case series presents two patients who developed iatrogenic intraoral hair after nasolabial flap reconstructions, resulting in mucosal irritation, difficulty maintaining oral hygiene, and emotional distress. Laser hair removal was not feasible due to technical limitations in the oral cavity. Instead, electrolysis was successfully employed as a permanent hair removal method. Both patients showed improvement after treatment, with one requiring a second session due to slight recurrence. Electrolysis is a practical and effective alternative to laser therapy for managing intraoral hair growth, particularly in cases where laser treatments are challenging.